Ha Uji Aktivitas Antibakteri Fraksi n-Heksan dan Etil Asetat Lichen (Parmotrema tinctoruma) terhadap Staphylococcus aureus dan Escherichia coli - Hamdayani L A; Subehan Subehan; Natsir Djide (STIFA Makassar, 2019)
Antibacterial activity of n-hexane and ethyl acetate Lichen (Parmotrema tinctoruma) has been tested on Staphylococcus aureus and Escherichia coli. The fraction was obtained from the liquid-liquid partitioning of Lichen ethanol extract (Parmotrema tinctoruma) which had gone through a maceration stage with 70% ethanol extraction. The liquid partitioning process is carried out using n-hexane and ethyl acetate. Antibacterial activity testing was carried out by agar diffusion method. Chemical components in the most active fractions are identified through phytochemical screening by thin-layer chromatography methods. The antibacterial activity test showed that the fractions of Lichen were able to inhibit the growth of the bacteria Staphylococcus aureus and Escherichia coli. The n-hexane and ethyl acetate fractions each had inhibition zones of 14.50 mm and 11.37 mm. The Identification of compounds in the most active fraction through thin layer chromatography showed the presence of flavonoid compounds.